Correlations among microfibril angle, density, modulus of elasticity, modulus of rupture and shrinkage in 6-year-old Eucalyptus urophylla × E. Grandis - Hein, P.R.G.; Silva, J.R.M.; Brancheriau, L. (Maderas. Ciencia y Tecnología, 2025)
The cellulose microfibril angle (MFA) in the cell wall is known to have major effects on wood stiffness and shrinkage. However, its influence on juvenile wood traits is not fully understood, especially in Eucalyptus. The aim of this study was to evaluate the relationships among MFA, density (ρ), dynamic modulus of elasticity (E), modulus of rupture (MOR), and shrinkage (δ) in 6-year-old Eucalyptus urophylla × E. grandis. Small clear specimens (L 410 mm x R 25 mm x T 25 mm) were cut from central boards for the determination of E and MOR. Cubic samples (25 mm³) were removed after the dynamic and static tests to evaluate ρ and δ. MFA was finally measured by X-ray diffraction on small strips coming from the cubic samples. A quasi-absence of statistical link was found for MFA - δ and MFA - ρ (R²<0.20). The parameter ρ/MFA was used to estimate E (R²=0.66) and MOR (R²=0.37). In a next step, the additive and interaction effects were investigated using multiple linear regressions with a forward selection method. The property E was found to be linked only with the additive effects of ρ and 1/MFA (R²=0.76). The additive and interaction effects were all significant for MOR (R²=0.54). This study showed that a general model including both additive and interaction effects should be used for the prediction of the modulus of elasticity and the modulus of rupture.